To study efficacy of foot temperature monitoring and footprint study in preventing diabetic foot ulcer in type 2 diabetic patients with peripheral neuropathy - Manjunath Ashok Kolachi; Sudhir Kumar; Albail Singh Yadav; Mandavi Agarwal (Asian Journal of Medical Sciences, 2025)
Background: Diabetic foot ulcers (DFU) are a common complication among diabetic patients, leading to an increased risk of amputation and mortality. About 15–25% of diabetics develop DFUs, with half of these cases requiring amputation. Early identification of high-risk patients, particularly those with peripheral neuropathy, is crucial in preventing DFUs. Non-invasive methods such as foot temperature monitoring and footprint analysis have shown promise in identifying these high-risk individuals. Aims and Objectives: This study aimed to evaluate the efficacy of foot temperature monitoring and footprint analysis in preventing DFUs in type 2 diabetic patients with peripheral neuropathy by identifying high-risk pressure points and temperature differences. Materials and Methods: A prospective study was conducted on 100 patients at Maharani Laxmi Bai Medical College, Jhansi, comprising 50 patients with diabetic neuropathy and foot ulcers and 50 patients with neuropathy but without ulcers. Foot temperature was monitored using a handheld infrared thermometer, while footprint analysis was conducted using a Harris mat. Patients were followed for 5 months to monitor the development of DFUs. Statistical analysis was performed using the Chi-square test, with a significance threshold of P<0.05. Results: Out of 50 neuropathic patients without ulcers, 14 (64%) developed DFUs, primarily in those with a foot temperature difference of >2°C and grade 3 or 4 pressure points. Foot temperature monitoring and footprint analysis showed a combined efficacy of 67% in predicting DFU development. The results were statistically significant (P<0.05). Conclusion: Foot temperature monitoring and footprint analysis are effective tools for predicting DFU development in diabetic neuropathy patients. Early identification of high-risk individuals allows for timely interventions, such as appropriate footwear, reducing DFU incidence and the associated risk of amputation.